Oxidative Stress and Decreased Mitochondrial Superoxide Dismutase 2 and Peroxiredoxins 1 and 4 Based Mechanism of Concurrent Activation of AMPK and mTOR in Alzheimer's Disease - Majd, Shohreh; Power, John H T (Current Alzheimer research, 2018)
Emerging evidence supports the hypothesis that metabolism dysfunction is involved in pathogenesis of Alzheimer's disease (AD). One aspect of metabolic dysfunction includes dysregulation of adenosine monophosphate kinase protein kinase (AMPK) and mammalian target of rapamycin (mTOR) metabolic axis, which is extensively present in some of the leading causes of AD such as cerebrovascular diseases, type 2 diabetes and brain ischaemic events. While the molecular basis underlying this metabolic dysregulation remains a significant challenge, mitochondrial dysfunction due to aging appears to be an essential factor to activate AMPK/mTOR signaling pathway, leading to abnormal neuronal energy metabolism and AD pathology. Using immunofluorescent imaging by Lecia confocal microscopy, we analyzed the activation of AMPK/mTOR. Concurrently, the level of mitochondrial antioxidant enzymes of superoxide dismutase 2 (SOD2) and peroxiredoxin 1 and 4 (p1 and p4) along with protein and DANA oxidation were examined to in postmortem brains of AD (n= 8) and normal (n= 7) subjects to evaluate the metabolism dysfunction role in AD pathology. In spite of AMPK inhibitory control on mTOR, concurrent phosphorylation of AMPK and mTOR (p-AMPK and p-mTOR) was observed in AD brains with high colocalization with hyperphosphorylated tau. Mitochondrial antioxidant enzymes of SOD2 and p1 and p4 were substantially decreased in p-AMPK, p-mTOR and p-tau positive cells along with higher levels of DNA and protein oxidation. Collectively, we conclude that AMPK and mTOR metabolic axis is highly activated in AD brains. While the inhibitory link between AMPK and mTOR seems to be disrupted, we suggest oxidative stress as the underlying mechanism for concurrent activation of AMPK and mTOR in AD.